Economic Situation in the Countries of Horn Africa and Kingdom Saudi Arabia (Research Bulletins of the Faculty of Economic Sciences, 2018)
The author briefly presented the economic and social situation in the countries of the Horn of Africa: Djibouti, Ethiopia, Eritrea and Somalia and showed how she reacted to newcomers from these countries Saudi Arabia.
Keywords: Horn Africa; Economy; Saudi Arabia; Middle East; Africa